AN ANALISIS MOTIVASI SISWA DALAM MEMBACA BAHASA INGGRIS - Sanaria Maneba; Nur Melansari; Baharudin Adu (English Education Department, 2021)
The problem in this research was how is students’ motivation in reading English at grade VIII SMP Negeri 4 Baubau. This research was descriptive qualitative research. The population of the research was grade VIII of SMP Negeri 4 Baubau which consisted of 11 classes with total 345 students. The sample in this research was taken with random sampling technique that was class VIII.1 which consisted of 25 students. The instrument used was Motivations for Reading Questionnaire (MRQ). The research outcome showed that 5 students out of the total student are in high motivation category, 13 students out of the total students are in average motivation level, and 7 students out of the total students are in low motivation level. Then, it can be concluded that the students’ reading motivation level is in the average motivation level.